2002
DOI: 10.1097/00004583-200208000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Community Study: Do Psychosocial Risk Factors and Child Behavior Checklist Scores at 5 Years of Age Predict Psychiatric Diagnoses at a Later Age?

Abstract: Vles, J. S. H. (2002). A longitudinal community study: do psychosocial risk factors and child behavior checklist scores at 5 years of age predict psychiatric diagnoses at a later age? Journal of the American Academy of Child and Adolescent Psychiatry, 41(8), 955-963. https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
3
42
0
2
Order By: Relevance
“…In another study, conducted with a community sample in the Netherlands, Kroes and colleagues followed five to six year old children for over one year and found that living in a single headed household, having a sibling, and experiencing a negative life event (type of specific life event was not evaluated) each emerged as separate significant predictors for anxiety disorders. 24 Finally, Shaw et al investigated the relation between negative life events assessed during infancy (15 months) and CBCL internalizing scores at five years of age among 86 low-income mother-child dyads (40% were African American). 17 The total number of negative events (the impact of individual events was not examined) proved to be a significant predictor of CBCL scores.…”
mentioning
confidence: 99%
“…In another study, conducted with a community sample in the Netherlands, Kroes and colleagues followed five to six year old children for over one year and found that living in a single headed household, having a sibling, and experiencing a negative life event (type of specific life event was not evaluated) each emerged as separate significant predictors for anxiety disorders. 24 Finally, Shaw et al investigated the relation between negative life events assessed during infancy (15 months) and CBCL internalizing scores at five years of age among 86 low-income mother-child dyads (40% were African American). 17 The total number of negative events (the impact of individual events was not examined) proved to be a significant predictor of CBCL scores.…”
mentioning
confidence: 99%
“…The CBCL identifi es very similar behavior problems after very preterm birth even when the children and their families are from diverse geographic and cultural backgrounds as is the case for the CAP study cohort [48] . Importantly, CBLC scores at 5 years of age are good predictors of psychiatric diagnoses at a later age [49] . CAP study children with Total Behavior Problems T scores 1 69 will be considered to have a disabling behavior problem.…”
Section: Test Details and Additional Outcomesmentioning
confidence: 96%
“…This tool is commonly used to measure behaviors of ex-preterm children [48][49][50][51] . The CBCL identifi es very similar behavior problems after very preterm birth even when the children and their families are from diverse geographic and cultural backgrounds as is the case for the CAP study cohort [48] .…”
Section: Test Details and Additional Outcomesmentioning
confidence: 99%
“…Diese etwas höhere Belastung der Familien mit MH steht im Einklang mit anderen nationalen und internationalen Studien [z.B. Kroes et al, 2002;RKI, 2008;Rydell, 2010;von Lersner et al, 2015;siehe auch Diehl et al, 2016;Belhadj Kouider et al, 2014;Stevens und Vollebergh, 2008]. Auffällig ist das höhere Ausmaß an körper-lichen Bestrafungsmethoden, das auch in anderen Studien festgestellt wurde [Pfeiffer et al, 1999;Wissow, 2001; siehe auch Diehl et al, 2016].…”
Section: Diskussionunclassified